Bridging Maqāṣid al-Sunnah in Contextual Hadith Commentaries: A Case Analysis of the Hadith on Humanity in the Divine Image - Muhid; Muhammad Fauzinudin Faiz; Suhermanto Ja'far; Hodri (UIN Sunan Kalijaga Yogyakarta, 2026)
The establishment of universal standards embedded in hadith—framed as legal objectives—underwent a process of generalization, wherein their function served to justify Qur'anic content. Consequently, the primary role of hadith as a lawmaker and moral guide was marginalized in discourses on goal-based (maqāṣid) development. This study seeks to identify a systematic method for interpreting hadith by drawing on the standards of its discursive construction, which accounts for the Prophet’s flexible role as a discourse producer. To this end, the study employs a qualitative methodology grounded in constructive grounded theory. It finds that the discourse of hadith transmission—centered on the conveyance of meaning—necessitates a model of textual verification (taḥqīq al-naṣṣ) as its core component. This mechanism involves tracing variant hadiths on the same theme to discern differences in editorial structure that influence their core and relational meanings. In turn, it facilitates the identification of interpretive models for key words and particles that convey meaning. Textual composition further demands a comprehensive examination of legal practices within the earliest recipient community to establish standards for means and ends. The application of these methodological standards yields a novel interpretive framework for hadiths concerning the creation of humans in God’s image. Specifically, the analysis of word patterns in their general and particular forms reveals an intentional prohibition on depicting the face, aimed at preserving human honor and dignity as God’s creations. Ultimately, clarifying these means and purposes creates space for innovative prohibition models that prevent fictitious or verbal acts degrading any aspect symbolizing humanity.